Analysis of Strategic Variables for the Development and Sustainability of Fos-Food Restaurant Business in the Pandemic Era; MICMAC Approach - Lina Asmara Wati; Riski Agung Lestariadi; Supriyadi Supriyadi; Muhammad Permana Hendra Safii (Journal of Aquaculture and Fish Health, 2023)
Talk about smart cities, the community's independence to open a business and drive the local economy is a concrete form in the community, which is useful in the current state. Even though in this Covid-19 pandemic condition, the life of a business is not easy, especially the seafood culinary business. A restaurant business requires a business development strategy that will determine the business's long-term future—this culinary tourism development and sustainability strategy. The MICMAC method functions analytically to solve systematic problems by developing sustainability strategies in industrial areas. So in this study, researchers will research Strategic Variable Analysis for the Development and Sustainability of the Fos-Food Restaurant Business in the Pandemic Era; MICMAC approach. This study uses primary and secondary data and uses the MICMAC method. The results of this study are: (1). The strategic factor analysis of Fos-Food Restaurant development has 11 strength variables, seven weakness variables, six opportunity variables, and eight threat variables. Based on the weighting and scores carried out, the total score for internal factors was 3.17 and for external factors was 3.07. (2). The research analyzed Fos-Food's development strategies and programs from the SWOT diagram, SWOT matrix, SWOT quadrant strategy analysis, and MICMAC analysis. The strategy analysis shows that the position of this restaurant is currently still in quadrant IV. Then the MICMAC analysis shows that judging from the indirect influence graph of each relationship between variables, the variables that have the greatest value are the variables: Financial and Accounting, Technological Environment, and Buyer/Customer Power.